THE ROLE AND EFFECT OF TELEGRAM AND KAHOOT PLATFORMS IN EFL CLASSROOMS - Anvarjon Isroilov G‘iyosidinovich, (TADQIQOTLAR, 2026)
Annotation This study investigates the effectiveness of Telegram and Kahoot platforms in English as a Foreign Language (EFL) classrooms. The research focuses on their impact on students’ motivation, engagement, and language skill development, particularly in grammar  and  vocabulary  acquisition.  A  mixed-method  approach  was  employed, including classroom observation, questionnaires, and pre-test/post-test analysis. The  findings  reveal  that  the  integration  of  these  digital  tools  significantly enhances  student  participation,  improves  vocabulary  retention,  and  creates  a  more interactive and engaging learning environment. Telegram supports continuous learning beyond the classroom, while Kahoot promotes active participation through gamified assessment. The study concludes that combining these platforms contributes to more effective and student-centered EFL instruction.